Revenue Relation with VAT in Nepal Government Budget Structure - Sangraula, Prem Prasad (Damak Campus Journal, 2023)
Taxes are major fiscal policy instruments and important government policy tools have an important role in increasing the rate of capital formation and thereby a high rate of economic growth can be achieved. Globalization, privatization and liberalization have brought the huge change in the country budget and economic environment. The budget management of government is one of the important tasks which play very important role in the nation and international environment which influence the technology and changing business environment has posed many challenges before management. This study aims to find out the Nepal government budget status in economic sectors. Descriptive research has been conducted using annual report of economic survey of ministry of finance. Descriptive analysis suggested that is strong relationship between revenue and expenditure management of Nepal government budget. The main objective of this study is to determine the relationship between revenue and expenditure in the study made over the period 2073/74 to 2077/78 taken as a sample year in this research study among the various fiscal years of Nepal government budget. The statistical methods of trend analysis and descriptive statistics like mean, standard deviation, coefficient of variation and hypothesis test were used to analyze the study outcomes. The results of the study indicated the revenue, expenditure and deficits conditions of Nepal government budget. This research articles report sources of revenue and structure of budget heads of Nepalese economic sector. It also reflects the whole revenue and expenditure positions of Nepal government and effective implementation of revenue estimation to manage deficits conditions. The revenue, expenditure and deficits conditions policy and strategies would also helps to manage deficits conditions by research studying.